PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP SUSTAINABILITY REPORT DENGAN MANAJEMEN LABA SEBAGAI VARIABLE INTERVENING PADA PERUSAHAAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2021-2023 - Maulani, Rizky; Tangngisalu, Jannati; Sulfati, Andi (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on the Sustainability Report with Earnings Management as an intervening variable. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A quantitative approach was used with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique using SmartPLS 4.0 software. The results show that CSR does not significantly affect earnings management or the Sustainability Report. GCG has a significant negative effect on earnings management but does not affect the Sustainability Report. Meanwhile, earnings management significantly influences the Sustainability Report. The mediation test results indicate that earnings management does not mediate the relationship between CSR or GCG and the Sustainability Report. This research implies that strong GCG practices can reduce earnings management, but further efforts are needed to integrate CSR and GCG into the quality of corporate Sustainability Report ing.